Applying Hsp104 to protein-misfolding disorders - Vashist, Shilpa (2010)
Hsp104, a hexameric AAA+ ATPase found in yeast, transduces energy from cycles of ATP binding and hydrolysis to resolve disordered protein aggregates and cross-β amyloid conformers. These disaggregation activities are often co-ordinated by the Hsp70 chaperone system and confer considerable selective advantages. First, renaturation of aggregated conformers by Hsp104 is critical for yeast survival after various environmental stresses. Second, amyloid remodeling by Hsp104 enables yeast to exploit multifarious prions as a reservoir of beneficial and heritable phenotypic variation. Curiously, although highly conserved in plants, fungi and bacteria, Hsp104 orthologues are absent from metazoa. Indeed, metazoan proteostasis seems devoid of a system that couples protein disaggregation to renaturation. Here, we review recent endeavors to enhance metazoan proteostasis by applying Hsp104 to the specific protein-misfolding events that underpin two deadly neurodegenerative amyloidoses. Hsp104 potently inhibits Aβ42 amyloidogenesis, which is connected with Alzheimer's disease, but appears unable to disaggregate preformed Aβ42 fibers. By contrast, Hsp104 inhibits and reverses the formation of α-synuclein oligomers and fibers, which are connected to Parkinson's disease. Importantly, Hsp104 antagonizes the degeneration of dopaminergic neurons induced by α-synuclein misfolding in the rat substantia nigra. These studies raise hopes for developing Hsp104 as a therapeutic agent.